Faktor-faktor yang mempengaruhi wisatawan melakukan kunjungan ke obyek wisata di kabupaten pacitan tahun 2014 - Wulandari, Dian Novita, Siti Fatimah NH, SE, M.Si (2016)
This study entitled "Analysis of Factors Affecting Travelers Conduct Visits to Pacitan Tourism in 2014". The purpose of this study is; (1) to analyze the effect of origin of tourists, transportation costs, income and age of travelers on tourist visits to attractions in Pacitan 2014;m(2) analyze the response of the tourist attractions in Pacitan. The research location is a tourist attraction Goa Gong, warm water bath and Teleng Ria beach. The sampling method is combined with Quota Sampling and Convenience Sampling with a sample size of 60 respondents each study site were taken by 20 respondents composed of 10 tourists, 5 business, 1 officer and 4 villagers. Data were obtained by spreading questionnaires and interviews In this study using multiple linear regression analysis model of Ordinary Least Square (OLS). The results of the analysis are: (1) The results of linearity test with Ramsey models Research shaped linear regression model; (2) The calculation data normality test with normal distribution model of Jarque Bera; (3) The test results showed the classical assumption that there are no issues multicolinearity, heterokedastisitas problems occur, and there is no problem of autocorrelation; (4) The results of t-test showed that the variables that significantly influence the frequency of visits by tourists is the variable of origin of tourists, transportation costs and variable income, whereas the rating variable age had no significant effect; (5) F test results showed that the model is in use exist; (6) R2 scored 97.51% which means that 97.51% of the variation frequency of tourists visit can be explained by the variable of origin of tourists, transportation costs, income and age rating, while the remaining 2.49% is explained by other variables outside the model estimated. Descriptive analysis of 30 respondents about the perception of tourists about the beauty of nature, cleanliness, security, service officer, facilities,and the accessibility of tourist attraction in Pacitan is 83.4% thought very beautiful, 60% thought quite clean, 50% thought the secure, 76.6% thought friendly, 60% thought quite complete, and 50% found easily.